Risk management in translation - Pym, Anthony 1956- (Cambridge elements, 2025)
Once fidelity and equivalence are abandoned, how can successful translation be understood? Risk management offers an alternative way of looking at the work of translators and their social function. It posits that the greater the cultural differences, the greater the risks of failed communication. What can be done to manage those risks? Drawing on the ways translators and interpreters handle intercultural encounters by adjusting what is said, this essay outlines a series of strategies that can be applied to all kinds of cross-cultural communication. Practical examples are drawn from a wide range of contexts, from Australian bushfires to court interpreting in Barcelona, with special regard for the new kinds of risks presented by machine translation and generative AI. The result is a critical view of the professionalization of translation, and a fresh account of democratized translation as a rich human activity in the service of cross-cultural cooperation